How food export restrictions could worsen a looming food crisis - Hepburn, Jonathan; Laborde Debucquet, David; Parent, Marie; Smaller, Carin (International Institute for Sustainable Development, 2020)
This policy brief draws on analysis in the International Food Policy Research Institute’s (IFPRI’s) COVID-19 Food Trade Policy Tracker to examine how food-importing countries could be affected by recent measures to restrict exports.